Why are the commuting distances of power couples so short? An analysis of the location preferences of households. - Willemijn Van Der Straaten; Jan Rouwendal (European Regional Science Association (ERSA), 2010)
Couples of which both spouses are highly educated (so called 'power couples') face a more complex work-home relation than singles or single-earner households. However, the commuting time of power couples is relatively short. In this paper we analyze whether these power couples use their relatively large purchasing power to outbid other households from locations that are especially attractive to them, as is predicted by household location theory. Using a residential sorting model we estimate a residential location choice model in which households choose their residential location on the basis of natural and urban amenities as well as the accessibility of jobs. The model used allows for heterogeneity between households in the preferences of the characteristics of their residential location. The results show that an average household would like to live close to a large labour market, close to a railway station, in regions with a high regional wage, and have urban facilities. Households are indifferent with respect to the distance to the nearest highway slip road and the amount of nature. Power couples are willing to pay more than the average household in order to be located close to large labour markets and to have good urban facilities in their residential location. The results show that the location choice is not simply more connected with only the working place. Although accessibility to the workplace is still important, the amenities, that the location offers are also regarded as important; especially for power couples. And it explains why these couples are more likely to live in large urban areas.
Keywords: 330